AN ANALISYS OF COMMUNITY EMPOWERMENT ON THE SME MITRA UMAT PROGRAM OF LEMBAGA AMIL ZAKAT BANGUN SEJAHTERA MITRA UMAT (LAZNAS BSM UMAT) - Felita, Safira; Muhtadi, Muhtadi (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2022)
Community development through productive zakat could improve the economic state of mustahiks, particularly those with Small and Medium Enterprises (SMEs). This study aims to: (1) learn about the LAZNAS BSMU community development scheme; (2) understand the benefits and drawbacks of the Mitra Umat SME program. This study employs a qualitative approach with descriptive evaluative methods. Field research data collection techniques include observation, interviews, and documentation. According to the findings of this study: (1) Mitra Umat team from LAZNAS BSMU accomplished their program so well and managed productive zakat as it should and precisely through Mitra Umat SME program for the mustahiks who joined and participated in the program; (2) The mechanism of development done by Mitra Umat team LAZNAS BSMU suitable according to the theory of community development; and (3) Mitra Umat SME program based on productive zakat could give a good impact and welfare.